Assessment of tactical choices in women water polo - Raiola, G.; Di Tore, A.; Napolitano, S.; Izzo, R. (Science, Movement & Health, 2012)
In water polo lacks a codified methodology for tactics training, which is thus only left to coach`s discretion and expertise by a long time of experience. Nine women water polo matches, during season 2011/2012 Italian female Serie A1), have been analyzed by a water polo coach, helped by a statistician and a performance analyst. Purpose of the analysis process was to identify single events during the matches, to examine the tactical pattern implemented in this events, to obtain by the coach an evaluation on tactical pattern compliance and then to put this compliance in relation to event`s outcome. Aim of the work is to verify the efficacy of different attack patterns, when they were well-performed, in order to create a codified methodology for teaching water polo through tactics. The research method is integrated and consists of 3 distinct approaches: case study one of 9 matches of the Italian Serie A1 Women's Championship, season 2011/2012, played by the Volturno sporting club for the analysis of matches, action research one for coach contribution by working and analysis, and theoretical-argumentative one to deduce a framework in which define the data processing. The research team, composed by coach, statistical analyst, research designer and coordinator, examined matches with Dartfish TeamPro, isolating single key frames or indicators relative to attack events, identifying the implemented attack pattern, then the coach expressed an evaluation on attack pattern compliance. The results showed a general efficacy of tactical patterns when they are well performed), but showed significant differences within correlation coefficients of single patterns, confirming the need for developing a common methodology for teaching water polo through tactics.